Historia y mito en los últimos historiadores greco-judíos - Nieto Ibáñez, Jesús María (1995)
The Jewish historians select the most outstanding and glorious moments and characters of their mythical past, expounding them in Greek, the most spreading language of those times.
Keywords: Historiadores; Mito; Judíos